A Review on Blockchain’s Applications and Implementations - Ahmad, Pervez (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2021)
Blockchain Technology (BCT) is one of many other emerging technologies that were introduced in the past several years & carried loads of potential utilizing technological development. This paper describes in detail the progress made in Blockchain Technology. Keeping this in mind, some fields have been determined in which their efficiency and modernization can be promoted by using Blockchain Technology. It also describes the problems and challenges faced in implementing Blockchain Technology. Researchers are performing studies vigorously to discover all the possible proficiencies of Blockchain Technology with some of them having faith in the Blockchain being vital for a de-centralized civilization. This paper provides an overview of Blockchain’s applications.